Investigating native and exogenous compounds within skin tissue - Starr, Nichola (2017)
The skin is the most extensive and accessible organ in the human body. It efficiently provides a barrier to an external hostile environment whilst maintaining and regulating fundamental physiological functions. The sophisticated and complex nature of this natural barrier requires continued analytical advancement to offer further insight into both its biological mechanisms and how to target the delivery of compounds through it. This work presents the use of a recently emerging technique in the field of skin research, time of flight - secondary ion mass spectrometry (ToF-SIMS), to investigate the presence of both native and exogenous compounds in skin tissue from samples collected both in vivo and ex vivo.